The Effectiveness of Risk Management Practices in Financial Institutions: A Meta-Analysis - Nur, Ririn Apriana M. (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to evaluate the effectiveness of risk management practices in financial institutions through a meta-analysis approach to published studies. Using a systematic literature review methodology and PRISMA guidelines, this research identifies and analyzes data from a number of relevant studies, covering various types of risk such as credit, market, liquidity and operational risks. The results show that although risk management practices are generally effective, there are significant variations in such effectiveness depending on the type of financial institution and geographic context. These findings underscore the importance of adapting risk management practices to suit the specific characteristics of the institution and the risk environment it faces. This research also makes a theoretical contribution by filling the gap in the literature regarding the systematic evaluation of risk management practices, as well as offering practical implications that can be used for policy development in the financial sector.